2013
DOI: 10.1158/1538-7445.am2013-2077a
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2077A: MM141, a novel bispecific antibody co-inhibitor of IGF-1R and ErbB3, inhibits the proliferation of melanoma cells.

Abstract: Identification of druggable targets along with new therapies in metastatic melanoma is a main concern given the bad prognosis of this disease in the metastatic setting. The development of targeted therapies for cancer has fundamentally changed the ways in which we develop new drugs, select therapy for patients, design and conduct clinical trials and assess treatment outcomes. The problems can be most effectively attacked by an integrated approach that leads from discovery through preclinical and clinical devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, MM-141 has been proven to inhibit pancreatic tumor cell growth and potentiate of effect of gemcitabine in various preclinical models [ 144 ]. In addition, MM-141 has exerted its anti-proliferative activity against melanoma [ 145 ], and this antibody has also attenuated tumor growth and potentiated the activity of mTOR inhibitor everolimus in mouse models of anti-hormone therapy-resistant ER/PR + breast cancer [ 146 ]. Furthermore, previous studies with MM-141 have shown the ablation of HER3 signaling results in the inhibition of PI3K/AKT dependent mammary carcinogenesis and ERK1/2 phosphorylation in pre-neoplastic HER2 overexpressing mammary glands and tumors [ 91 , 147 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MM-141 has been proven to inhibit pancreatic tumor cell growth and potentiate of effect of gemcitabine in various preclinical models [ 144 ]. In addition, MM-141 has exerted its anti-proliferative activity against melanoma [ 145 ], and this antibody has also attenuated tumor growth and potentiated the activity of mTOR inhibitor everolimus in mouse models of anti-hormone therapy-resistant ER/PR + breast cancer [ 146 ]. Furthermore, previous studies with MM-141 have shown the ablation of HER3 signaling results in the inhibition of PI3K/AKT dependent mammary carcinogenesis and ERK1/2 phosphorylation in pre-neoplastic HER2 overexpressing mammary glands and tumors [ 91 , 147 ].…”
Section: Introductionmentioning
confidence: 99%